2022
DOI: 10.1002/batt.202200164
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Charge Carrier Mobility in d0‐Metal‐based Spinels

Abstract: Enabling high Mg ion mobility, spinel-type materials are promising candidates for cathode or solid electrolyte applications. To elucidate the factors governing the observed high mobility of multivalent ions, periodic DFT calculations of various charge carriers (A = Li, Na, K, Mg, Ca, Zn and Al) in the ASc 2 S 4 and ASc 2 Se 4 spinel compounds were performed, resulting in the identification of a Brønsted-Evans-Polanyi-type scaling relation for the migration barriers of the various charge carriers. Combining thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…The discovery of the defect formation energy as a significant feature for interstitial migration is noteworthy as it reflects a kind of Brønsted-Evans-Polanyi-type relation between activation energies and site preference of the charge carriers. [4] Overall, these analyses will aid in designing efficient electrodes and solid electrolytes by narrowing down the essential properties in a multidimensional design space. However, to extend the results beyond anti-perovskites, further research is necessary, such as incorporating dynamic phenomena like lattice vibrations and poly-anion rotations into the feature set.…”
Section: Descriptors and Design Principlesmentioning
confidence: 99%
See 3 more Smart Citations
“…The discovery of the defect formation energy as a significant feature for interstitial migration is noteworthy as it reflects a kind of Brønsted-Evans-Polanyi-type relation between activation energies and site preference of the charge carriers. [4] Overall, these analyses will aid in designing efficient electrodes and solid electrolytes by narrowing down the essential properties in a multidimensional design space. However, to extend the results beyond anti-perovskites, further research is necessary, such as incorporating dynamic phenomena like lattice vibrations and poly-anion rotations into the feature set.…”
Section: Descriptors and Design Principlesmentioning
confidence: 99%
“…Such improvements are evident in the low migration barriers of Ca in d 0 ‐metal oxide spinels. [ 4 ] Migration barriers in spinel materials have recently been used to derive a descriptor for the ion mobility based on ionic radii, oxidation states, and electronegativities, as mentioned in the previous section. [ 3 ] Additionally, it was shown that transport properties of spinel compounds are impacted by transition metal cations, discovering that these metals have a notable impact on the barriers for Mg 2+ migration in such compounds.…”
Section: Materials Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…This high electronic conductivity poses a challenge for its practical application as it leads to significant self-discharge. [16] In our earlier work, we estimated the self-discharge for a charged Mg|MgSc 2 Se 4 |Mo 6 S 8 battery and found that 10% of the total charge capacity would be lost within a short duration of 16 h. [18] Due to the promising ionic conductivity of MgSc 2 Se 4 reported by Canepa et al, follow-up works have been carried out to gain a more comprehensive understanding. Wang et al employed two routes of compositional tuning to suppress the electronic conductivity of MgSc 2 Se 4 , but neither method was successful.…”
Section: Introductionmentioning
confidence: 99%